Update on Fc-Mediated Antibody Functions Against HIV-1 Beyond Neutralization - Su, Bin; Dispinseri, Stefania; Iannone, Valeria; Zhang, Tong; Wu, Hao; Carapito, Raphael; Bahram, Seiamak; Scarlatti, Gabriella; Moog, Christiane (Frontiers in Immunology, 2019)
Antibodies (Abs) are the major component of the humoral immune response and a key player in vaccination. The precise Ab-mediated inhibitory mechanisms leading to in vivo protection against HIV have not been elucidated. In addition to the desired viral capture and neutralizing Ab functions, complex Ab-dependent mechanisms that involve engaging immune effector cells to clear infected host cells, immune complexes, and opsonized virus have been proposed as being relevant. These inhibitory mechanisms involve Fc-mediated effector functions leading to Ab-dependent cellular cytotoxicity, phagocytosis, cell-mediated virus inhibition, aggregation and complement inhibition. Indeed, the decreased risk of infection observed in the RV144 HIV-1 vaccine trial was correlated with the production of non-neutralizing inhibitory Abs, highlighting the role of Ab inhibitory functions besides neutralization. Moreover, Ab isotypes and subclasses recognizing specific HIV envelope epitopes as well as pecular Fc-receptor polymorphisms have been associated with disease progression. These findings further support the need to define which Fc-mediated Ab inhibitory functions leading to protection are critical for HIV vaccine design. Herein, we review the different inhibitory properties of HIV-specific Abs that may potentially contribute to HIV protection.